SYSTEM OF FACTORS FOR FORMING THE PERSONALITY OF A CRIMINAL (Bulletin of criminological association of Ukraine, 2023)
It was found that the personality of a criminal is a complex of personal characteristics that determine motivations, values, skills, abilities and other personal qualities that stimulate criminal behavior.In general, it is most appropriate to include the following as factors that influence the formation of a criminal's personality: a) social factors: birth in a dysfunctional family; low level of education; lack of work, belonging to criminal groups; ethnic and cultural characteristics, etc.; b) psychological factors: reduced level of empathy, aggressiveness, imbalance; low level of self-control; depression; hangover; etc; b) emotional factors: fear, resentment, hatred, jealousy, desire for revenge, etc.; c) biological factors: genetic abnormalities; mental disorders; brain diseases and other diseases; d) situational factors: excessive workload; stressful situations; difficult financial situation; availability of weapons, etc.It is emphasized the fundamental need to understand the identity of the criminal in the newest crimes for domestic criminology, as well as those that have undergone a significant transformation due to digitalization, scientific and technological progress and special challenges in the conditions of martial law.
Keywords: the person of the criminal; crime; criminality; criminal group; factors